Tinjauan Kebutuhan Air Irigasi Persawahan (Studi Kasus: Desa Mekar Jaya, Kecamatan Baito, Kabupaten Konawe Selatan) - Angga Ashari Idrus; Uniadi Mangidi; Erich Nov Putra Razak (MEDIA KONSTRUKSI, 2024)
Review of Irrigation Water Needs in Rice Fields in Mekar Jaya Village, Baito District, South Konawe Regency. This research was conducted to determine the level of irrigation water needs in rice fields with an irrigation area of 80 ha. The analysis of irrigation water needs was carried out by applying rice planting patterns in early March and August. The analysis model used is crop water needs, water needs in land preparation, water availability and existing irrigation functions. From the results of the analysis of irrigation water needs of mekar jaya village with a maximum planned area of 80 ha of irrigated land, with rice - rice cropping patterns at the beginning of the March and August growing season experiencing a deficit (lack of water) with a discharge of 0.96 lt/Sc/ha.